2014
DOI: 10.1007/978-3-319-09330-7_37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Advanced Artificial Neural Network Classification and Feature Extraction Techniques for Detecting Preterm Births Using EHG Records

Abstract: Abstract. Globally, the rate of preterm births is increasing and this is resulting in significant health, development and economic problems. Current methods for the early detection of such births are inadequate. However, there has been some evidence to suggest that the analysis of uterine electrical signals, collected from the abdominal surface, could provide an independent and easier way to diagnose true labour and detect when preterm delivery is about to occur. Using advanced machine learning algorithms, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other studies have found medium frequency to be more helpful in determining whether delivery was going to be term or preterm [6], [15]. These along with amplitude based features, root mean squares, and sample entropy will be considered and extracted from the raw EHG signals.…”
Section: B Data Pre-processing/feature Extractionmentioning
confidence: 99%
“…Other studies have found medium frequency to be more helpful in determining whether delivery was going to be term or preterm [6], [15]. These along with amplitude based features, root mean squares, and sample entropy will be considered and extracted from the raw EHG signals.…”
Section: B Data Pre-processing/feature Extractionmentioning
confidence: 99%